The Common Cichory (Cichorium intybus L.) as a Source of Extracts with Health-Promoting Properties—A Review - Janda, Katarzyna (Molecules, 2021)
Natural products are gaining more interest recently, much of which focuses on those derived from medicinal plants. The common chicory (Cichorium intybus L.), of the Astraceae family, is a prime example of this trend. It has been proven to be a feasible source of biologically relevant elements (K, Fe, Ca), vitamins (A, B(1), B(2), C) as well as bioactive compounds (inulin, sesquiterpene lactones, coumarin derivatives, cichoric acid, phenolic acids), which exert potent pro-health effects on the human organism. It displays choleretic and digestion-promoting, as well as appetite-increasing, anti-inflammatory and antibacterial action, all owing to its varied phytochemical composition. Hence, chicory is used most often to treat gastrointestinal disorders. Chicory was among the plants with potential against SARS-CoV-2, too. To this and other ends, roots, herb, flowers and leaves are used. Apart from its phytochemical applications, chicory is also used in gastronomy as a coffee substitute, food or drink additive. The aim of this paper is to present, in the light of the recent literature, the chemical composition and properties of chicory.